India-Nepal Trade Dynamics and Exchange Rate Pass-through: Time-Varying Analysis of the Parameter - Adhikari, Reena; Adhikari, Gyan Mani; Dhungana, Agya (International Research Journal of MMC, 2026)
This paper analyses the exchange rate pass-through (ERPT) to consumer prices in Nepal by a Time-Varying Parameter Vector Autoregression (TVP-VAR) model. Adopting a quantitative research design, the study drew on monthly secondary data sourced from the Nepal Rastra Bank, the Central Bureau of Statistics of Nepal, and international databases, covering the period from January 2000 to October 2023. The data were analysed using Bayesian estimation through Markov Chain Monte Carlo (MCMC) simulation within the TVP-VAR framework with stochastic volatility. Since Nepal is a country with a fixed exchange rate pegged to the Indian Rupee and it has been integrated through trade at a huge rate with India, it is important to understand how the ERPT works in the monetary policy formulation. Three main findings in our empirical results include the first finding that when there is exchange rate depreciation, there are moderate consumer price increases, and the effect is realized in a period of twelve months. Second, there is a high time dispersion of ERPT, which reduces considerably during the initial stage after the monetary policy credibility improved with the establishment of a monetary policy structure and greater integration of the global value chain. Third, asymmetric shocks are strong with pass-through being much higher during depreciation than when there is appreciation, implying adhesive downward price changes. The research adds to the scanty empirical evidence on ERPT in landlocked developing economies and gives practical initiatives to the inflation-targeting regimen of Nepal Rastra Bank. The results highlight the need to have an effective monetary policy and to strengthen institutions to reduce the inflationary effects of external shocks.